X-ray spectroscopy for the magnetic study of the van der Waals ferromagnet CrSiTe3 in the few- and monolayer limit. (1st October 2022) - Fujita, Ryuji; Liu, Jieyi; Hou, Xiaofei; Guo, Yanfeng; Herrero-Martín, Javier; van der Laan, Gerrit; Hesjedal, Thorsten
Abstract: The study of magnetic order in few- and monolayer van der Waals materials poses a challenge to the most commonly employed magnetic characterization techniques as they normally lack magnetic sensitivity and/or lateral resolution enabling their thickness-dependent probing. Here we demonstrate the usefulness of x-ray absorption spectroscopy (XAS) and x-ray magnetic circular dichroism (XMCD) measurements, carried out at the Cr L 2, 3 and Te M 5 edges, for the study of the ferromagnetic semiconductor CrSiTe3 (CST) in the form of single- and few-layer flakes. By scanning the sample under the incident x-ray beam, a map of the exfoliated system was obtained, which reproduced the optical micrographs showing the detailed distribution and thicknesses of the flakes. In this way, XAS/XMCD was performed at selected sample areas, revealing the thickness-resolved spectroscopic and magnetic properties of the flakes, such as the spin and orbital magnetic moments. The spin moment, in line with the saturation field, is decreasing with film thickness, revealing a single-domain and out-of-plane magnetization for the thinnest films. For CST, the electronic properties are governed by the strong covalent bond between the Cr 3 d ( e g ) and Te 5 p states, giving rise to a superexchange scenario. We observed a gradually increasing ratio of orbital to spin moment for thinner flakes, which could be due to a further increase of the covalent mixing. Hysteresis loops were recorded at the Cr L 3 edge, showing an open loop for 10 down to ∼3 layers, while the bulk shows a wasp-waist shaped loop. With the transition temperature from the soft to the hard ferromagnetic state decreasing with thickness, the monolayer shows a narrowed, closed loop at 10 K, suggesting its transition temperature > 10 K. Our study demonstrates the unique capabilities of XAS/XMCD for the study of few-layer van der Waals magnets, highlighting the interplay between electron correlation and ferromagnetism in CST.